Claim Payment Administration Procedure At PT. Prudential Life Assurance Binjai Branch - Sallimah Ika Putri Malau; Yusrizal Yusrizal (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Administrative procedures for payment of life insurance claims to the insured at PT. Prudential Life Assurance Binjai Branch. Every decision made by humans is full of risks. The problem studied is how the administrative procedures for payment of life insurance claims and what obstacles are faced in the payment of life insurance claims at PT. Prudential Life Assurance Binjai Branch. The research method used is the empirical legal research method. The sources of data in this study are primary data obtained directly from field research in the form of statements or interviews from related parties in this study while secondary data comes from library research through legislation, literature, books and official documents. From the results of this study it was concluded that the implementation of life insurance claim payments is contained in standard life administration operating procedures, claims are accepted if the documents and claim forms submitted are complete and the obstacles that are often encountered in submitting life insurance claims are documents, forms and identities that do not match and taking too long to file a claim.